On Other Pathways and New Alliances (2009)
On May 21, 2009, Chris Gary from the Kinderbüro (children's office in Vienna, Austria) sent an email to EAFIT Children's University inviting us to be part of the programs Kinderunion tour and Kinderuni Wien. Besides, we were also invited to join the “mentoring association”, an alliance between peers from the different children's universities.